2012
DOI: 10.1111/j.1748-7692.2011.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment and postrelease monitoring of 11 mass stranded dolphins on Cape Cod, Massachusetts

Abstract: The health, postrelease movements, and behavior of mass stranded Atlantic white‐sided dolphins (Lagenorhynchus acutus) and short‐beaked common dolphins (Delphinus delphis) from Cape Cod, Massachusetts, were evaluated. Health was assessed through physical examination and blood analysis. Eleven dolphins (eight white‐sided dolphins and three common dolphins) were relocated, outfitted with satellite transmitters, and released during seven mass stranding events. Five transmitters recorded only location, and six als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…Sampson et al (2012) have demonstrated the utility of assessing health on the beach to decide if individual dolphins are releasable, and they have tested their judgments through post-release monitoring involving satellite-linked tracking. Our findings from at least one of the two pilot whales released from the stranding site after on-site health assessment suggest that the animal survived and returned to patterns typical of pilot whales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sampson et al (2012) have demonstrated the utility of assessing health on the beach to decide if individual dolphins are releasable, and they have tested their judgments through post-release monitoring involving satellite-linked tracking. Our findings from at least one of the two pilot whales released from the stranding site after on-site health assessment suggest that the animal survived and returned to patterns typical of pilot whales.…”
Section: Discussionmentioning
confidence: 99%
“…In two such cases, marked individuals subsequently restranded at other locations, up to several weeks post-release (Fehring & Wells, 1976;Irvine et al, 1979). Sampson et al (2012) evaluated the health of stranded Atlantic white-sided dolphins (Lagenorhynchus acutus) and short-beaked common dolphins (Delphinus delphis) from mass strandings on Cape Cod, Massachusetts, and then performed satellite-linked follow-up tracking. They determined that it is reasonable to expect that at least some mass-stranded dolphins in stable physical and physiologic condition can be relocated and released on the same day as stranding, and that they will resume behavior and habitat use that is typical of the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was not found restranded in the days following, and given its better health status compared to animal #2, we can hypothesize that it may have survived. This hypothesis is supported by the example of the false killer whales in Florida and recent demonstrations through satellite tracking and monitoring of the successful release of stranded animals in Australia and the U.S., in spite of their poor conditions (Gales et al, 2012;Sampson et al, 2012). The withdrawal of animal #2 on 1 February was artificial, but we can hypothesize that its natural death would have had the same consequence of releasing animal #1.…”
Section: Mitigation Of Mass Strandingsmentioning
confidence: 71%
“…Behavioural studies have also been used to complement physical examinations and blood analyses to assess the fitness o f stranded dolphins (Sampson et al, 2012). Beluga whale behaviour is particularly difficult to document in the wild because beluga whales spend approximately 85 % of their time below water (Kingsley et al, 2001 This study documented one case in which a beluga whale was observed to behave very unusually after it was harpooned.…”
Section: Behavioural Observations As Complementary Line Of Evidencementioning
confidence: 94%